Birt–Hogg–Dubé syndrome with rare unclassified renal cell carcinoma: A case report. Issue 51 (23rd December 2021) - Ren, Shangqing; Luo, Cheng; Wang, Yaoqian; Wei, Yi; Ou, Yong; Yuan, Jiazheng; Li, Xinglan; Wang, Junyao; Lv, Qian; Yang, Bo; Fan, Shida; Zhou, Fang; et al.
Abstract: Introduction: Birt-Hogg-Dubé syndrome (BHDS) is a rare genetic disease. Renal cell carcinoma is the most serious complication of BHDS. The histological types of BHDS-related renal cell carcinoma are mostly mixed chromophobe/eosinophil and chromophobe cell types. BHDS with unclassified renal cell carcinoma is extremely rare. Patient concerns: A 37-year-old man was admitted to the hospital because of lumbago and hematuria. Diagnosis: Combined with abdominal enhanced CT and pulmonary CT, BHDS complicated with renal cell carcinoma was diagnosed, and right partial nephrectomy was performed. The postoperative pathological diagnosis was unclassified renal cell carcinoma. Gene detection revealed the FLCN frameshift mutation. Outcomes: No signs of recurrence were observed after regular follow-up. Conclusion: The pathogenesis of BHDS has not been fully elucidated, and the pathological type of BHDS with unclassified renal cell carcinoma is extremely rare. Through case presentation and review of related literature, this paper summarizes the diagnosis and treatment of BHDS complicated with unclassified renal cell carcinoma.